PENGARUH KEMAMPUAN KERJA DAN SIKAP KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BIMA - Dewi Puspitasari; Wulandari Wulandari (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to analyze the effect of work ability and work attitude on employee performance at the Department of Population and Civil Registration of Bima Regency. The sampling technique used is the sampling technique used in the study using Non Probability Sampling with the number of samples used, namely 38 ASN employees. The methods used in this study are validity, reliability, classical assumptions, multiple linear regression, t-test and f-test. The partial test results reveal that the work attitude variable has a positive and significant effect on work performance. simultaneously (simultaneously) have a significant effect on work performance at the Department of Population and Civil Registration of Bima Regency.